Sensitivity Analysis to Determine the Prospect of Tollroad Investment: Case Study Krian-Legundi-Bunder-Manyar Tollroad - Yusuf Hartoyo; Christiono Utomo (IPTEK Journal of Proceedings Series, 2020)
PT Waskita Bumi Wira as the Toll Road Business Entity (BUJT) is investing in the Krian-Legundi-Bunder-Manyar Toll road with a viability gap fund (VGF) scheme. In the 2016 Toll Road Concession Agreement (PPJT) between BPJT-BUJT-PII, several acceptable investment variables have been agreed, namely: total investment value = Rp12,224,389,000,000, average daily traffic volume (LHR) = 21,874 vehicle / day, loan interest = 12.5%, toll tariff for group 1 = Rp1,250 / km, internal rate of return on equity (IRRonEquity) = 17.64%, payback period of 14 years and net present value (NPV) = Rp. 3,731,695,000,000. During the construction, there was a design change and a delay in land acquisition, this causes cost overrun. With a concession period of 45 years, inaccurate risk factors in the prediction of traffic volume growth rates, specific and non-specific risk factors and other uncertainties greatly affect the investment prospects. Therefore investment needs to be reviewed before this toll road is divested in 2025 by sharpening the minimum attractive rate of return (MARR) and LHR variables, then comparing them with the initial business plan. The estimated selling price of the divestment is also examined in this study. The investment valuation criteria that will be used in the sensitivity analysis are NPV and IRRonEquity. The approach in determining MARR is the use of MARRpremium = 15.81%. Sensitivity analysis with a deterministic approach is carried out to obtain limits on changes in investment costs, land acquisition costs, LHR traffic, loans (syndicated loans) to NPV in several tariff scenarios. This research shows that the NPV value is very sensitive to changes in investment costs. It is also known that in the toll tariff scenario according to PPJT compensation can be given in one of the conditions: investment costs increase by more than 7%, LHR traffic is less than 75%, or an increase in loans (syndicated loans) of more than 9%. The analysis of the stochastic approach shows that the probability of not exceeding the investment budget revenue limits due to changes of 37.29% to 46.56%.